Thank God We Are in Syria!' Modernization, Interfaith Relations and Women's Rights in Syria Before the Arab Spring' (2000-2010) - Ventura, Lorella (Islam and Christian-Muslim relations, 2018)
The status of women is generally considered a measure of modernity' and it has often been exploited by the West to highlight the backwardness' of non-Western countries and to justify colonialism and civilization' endeavours. The question of women's rights and its connection to modernity', however, is not simple. This article considers the example of Syria immediately before the revolts of 2011, and highlights that the government's approach to the issue of women's rights appears to have been inspired by a peculiar idea of modernity' that is not in line with the Western mainstream view, because it is not based on the centrality of the individual and does not include a view of secularization that underestimates the social and political importance of religious beliefs. Reflections on the peculiarities of the Syrian approach may help avoid simplifications and - more generally - may help us reflect on the premise of the mainstream Western approach to the issue in countries considered as other'.